(untitled) (Al-Academy, 2016)
Highlights This research highlights the important topic of musical topics that rarely talk about a musician, an issue of national songs which sang since the founding of the Iraqi state and until the end of the monarchy in Iraq, and wrote about just newspaper articles explaining the political situation experienced by the era of the history of Iraq and passing quickly marginally on the songs and patrons, so you see the researcher need to search for what was published around any way to see the texts of songs and melodies and rhythms and thus the possibility of evaluation, linked with the course of social and political life spiraling events at the time, so as not to miss these musical and literary, artistic and cultural features of forever also lost a lot of cultural and artistic heritage in the field of music and singing, and in the light of those justifications researcher found the need to conduct a study on the subject of national anthems in Iraq identified researched the title the following: (products of composers national anthems pioneers in Iraq